Characterization of Phosphate Membrane Transport in Saccharomyces cerevisiae CEN.PK113-5D under Low-Phosphate Conditions Using Aerobic Continuous Culture - Soheila Shokrollahzadeh; Farzaneh Vahabzadeh; Babak Bonakdarpour; Mehri Sanati; Bengt L Persson (Iranian Journal of Chemistry & Chemical Engineering, 2005)
Two different growth media, namely complex and defined media, were used to examine establishment of steady-state conditions in phosphate-limited culture system of Saccharomyces cerevisiae CEN.PK113-5D strain. Using the defined growth medium, it was possible to obtain steady state condition in the continuous culture. The effect of phosphate concentration on the growth of S. cerevisiae in phosphate-limited chemostat was studied at dilution rates between 0.08-0.45 h–1. The cells' growth followed Monod kinetics only over low dilution rates (0.08-0.22 h–1) in which the saturation constant (KS ) and maximum growth rate (μm ) were determined as 10 µM and 0.25 h–1, respectively. By increasing the dilution rates above 0.22 h–1, a significant change in the growth pattern was occurred, possibly due to intracellular accumulation of phosphate and/or extracellular accumulation of ethanol and also increased fermentative activity of the yeast cells. Phosphate transport of the yeast cells via plasma membrane transporters was kinetically characterized in a phosphate-limited chemostat culture. The rate of phosphate transport was measured using 32[P]-labeled orthophosphate in the concentration range of 0.4-2000 µM. High-affinity phosphate transport kinetics was observed over the entire range of dilution rates tested in this study. The corresponding Km values for phosphate were found to be in the range of 1.7 to 36 µM. Dilution rate of 0.22 h–1 showed biphasic pattern for phosphate uptake kinetics while the estimated Km values for this behavior were 1.7 and 284 µM.